Presentation of Empirical Equations for Estimating Internal Friction Angle of SP and SC Soils in Mashhad, Iran Using Standard Penetration and Direct Shear Tests and Comparison with Previous Equations - Salari, Pouya; Lashkaripour, Gholamreza; Ghafoori, Mohammad (International Journal of Geography and Geology, 2015)
Presentation of empirical equations for estimating engineering properties of soils is a simple, low cost and widely-used method. One of the major concerns in using these equations is evaluating their accuracy in different conditions and regions which often leads to doubts about obtained results. Most of these equations were derived in special laboratories, different climate conditions and in soils with different geotechnical and geological engineering properties and were generalized to other conditions. The main question is that whether these methods are also applicable to other conditions. Using local equations and narrowing the usage range of various methods based on each region properties are appropriate methods to solve these problems. This leads to simplified and faster analysis and high reliability in the obtained results. In this paper, empirical equations were derived to estimate internal friction angle, based on SPT numbers of Mashhad City’s soils in Iran, using SPT and direct shear tests results from 50 samples (25 SP and 25 SC soils samples). The results showed similar values for predicted φ values by SPT test and φ values determined by direct shear tests.